Some Ratios of Blood Components and their Correlation to the Special Endurance of the Block Skill in Volleyball - Bassem Hassan Ghazi (Journal of Global Pharma Technology, 2018)
The research included four sections as the research dealt with some physiological problems that affect the level of players to the skill of block when repeated several times during the game.The Aim of Research is toIdentify the levels of endurance to the block and blood components of the players of the Faculty of Physical Education and Sports Sciences in the volleyball / University of Kufa.To identify the relationship between the components of blood in search and endurance of the block in the volleyball.As for the imposition of the research, there is a significant correlation between the blood components and endurance of the block in the volleyball.The researcher chose the descriptive approach to suit the nature and problem of the research. The researcher selected the research sample from the research society represented by the players of the Faculty of Physical Education and Sports Sciences / Kufa University in the volleyball for the academic year 2017-2018 and the number of (12) player was selected (8)players ,they represent (66.66%) of the research community. And thus represent it genuinely.The Most Important ConclusionsThe proportion of hemoglobin in volleyball players has to do with the endurance of the block.The blood viscosity of volleyball players has to do with the special endurance of the block.There is no significant correlation between the endurance of the block and the number of white blood cells and red platelets.As for hypothesis of the research, there is a significant correlation between the blood components and endurance of the block in the volleyball.The Most Important RecommendationsEmphasis on the level of health of players, especially blood components because of the impact on the levels of players in various skills.Conduct periodic tests and tests for the players to check their blood components.The use of medical treatment when there is a weakness in the proportions of blood components by specialists.Keywords: Blood components, Special endurance and block skill.